Analysis of phenotypic stability in ten cassava genotypes in three West African countries - Asante, K.; Dixon, Alfred G.O. (2002)
Ten Cassava (Manihot esculenta, Crantz) genotypes were assessed for phenotypic fresh tuber yield stability for 2 years in nine locations in three West African countries (Nigeria, Ghana and Benin). From a combined analysis of variance for fresh yield, all main effects were significant. First order interaction genotype x year was not significant, while genotype and location interaction was significant. By Finlay and Wilkinson'sb-values tability statistic 82/00058 was considered highly yielding with average stabilityand may perform well in any of the three agroecologies. Genotypes 4(2) 1425 and 50395 would be adapted by any favourable agroecology by Finlay and Wilkinson's stability statistic. By Shukula's stability statistic, genotype 30572 ranked the most highly stable. The three stability statistics, Finlay and Wilkinson's, Shukula's and the rank sum method agreed in classifying genotypes 82/00661, 30572, 82/00942 and 82/00058 as high yielding and stable. A plot of environmental mean yields against coefficient of variation (CV) percent judged genotype 82/00942 as having phenotypic yield stability for the environments considered, while genotype 50395was judged less stable but high yielding, and, therefore, can be targeted to a specific agroecology.